Japan's Challenging Debt Dynamics - Guillemette, Yvan (OECD Publishing, 2013)
This working paper presents the background and the details of the simulations behind Box 1.4 of the May 2013 OECD Economic Outlook. A small simulation model is used to evaluate the contribution that the three pillars of the government's strategy - fiscal consolidation, growth-boosting structural reforms and higher inflation - could make to reversing the rise in Japan's public debt ratio, currently about 230% of GDP. The findings indicate that fiscal consolidation amounting to around 10 percentage points of GDP is necessary by 2020 to eliminate the primary deficit, as targeted in the current medium-term fiscal strategy. With moderately higher growth coming from increased female labour force participation and higher productivity growth, as well as inflation gradually rising to 2% thanks to unconventional monetary policy measures, the debt ratio would likely be put on a resolute downward trajectory by the end of this decade, although it is likely to remain around 200% of GDP in 2035
Keywords: Economics; Japan